Peran Serta Warga Negara dalam Pengambilan Kebijakan Publik - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ahmad Syahril Alfani; Muhamad Jalaludin; Solahuddin Dueramae (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This journal defines public policy as actions taken by governmental authorities to address specific social issues and emphasizes citizen participation as a key element in the democratic process. It outlines the importance of community involvement in policymaking to enhance legitimacy, governmental accountability, and the quality of policies. Factors influencing citizen participation include education, socioeconomic status, and access to information. The theoretical framework underscores the significance of active participation for successful community development, particularly highlighting the role of Generation Z in political engagement through digital platforms.Various methods for involving citizens in decision-making—such as public forums, surveys, and online platforms—are discussed, alongside the benefits of integrating technology to promote transparency and inclusivity. To explore this phenomenon in depth, a qualitative research method with an exploratory case study approach is employed. The study involves in-depth interviews with key informants such as public officials, representatives of civil society organizations, and Generation Z citizens who are actively engaged in digital participation. Additionally, participatory observation of public policy forums and documentation of various technology-based participatory initiatives are conducted. Thematic analysis is used to identify patterns, themes, and factors that influence the effectiveness of citizen participation in policymaking. Data validity is ensured through source and method triangulation, as well as member checking with selected respondents.This paper also presents case studies of successful participatory initiatives while addressing challenges such as unequal power dynamics and limited access to information. The recommendations focus on strategies to raise awareness, enhance transparency, encourage inclusivity, and foster a culture of active participation to ensure that policies reflect the diverse needs of society. Overall, meaningful citizen engagement is deemed essential for effective governance and policymaking.